Randomized comparison of atrioventricular node re-entry tachycardia and atrial flutter catheter ablation with and without fluoroscopic guidance: ZeroFluoro study - Lehar, Frantisek; Szegedi, Nándor; Hejc, Jakub; Jez, Jiri; Soucek, Filip; Kulik, Tomas; Siruckova, Anna; Sallo, Zoltan; Nagy, Klaudia Vivien; Merkely, Bela; Geller, László; Starek, Zdeněk (Europace, 2022)
AIMS: Interventional cardiology procedures may expose patients and staff to considerable radiation doses. We aimed to assess whether exposure to ionizing radiation during catheter ablation of supraventricular tachycardia (SVT) can be completely avoided. METHODS AND RESULTS: In this prospective randomized study, patients with SVT (atrioventricular re-entrant tachycardia n = 94, typical atrial flutter n = 29) were randomly assigned in a 1:1 ratio to catheter ablation with conventional fluoroscopic guidance (CF group) or with the EnSite Precision mapping system [zerofluoro (ZF) group]. Acute procedural parameters, increased stochastic risk of cancer incidence and 6-month follow-up data were assessed. Between May 2019 and August 2020, 123 patients were enrolled. Clinical parameters were comparable. Median procedural time was 60.0 and 58.0 min, median fluoroscopy time and estimated median effective dose were 240 s vs. 0 and 0.38 mSv vs. 0 and arrhythmia recurrence was 5% and 7.9% in the CF and ZF groups, respectively. The acute success rate was 98.4% in both groups. No procedure-related complications were reported. At an average age of 55.5 years and median radiation exposure of 0.38 mSv, the estimate of increased incidence was approximately 1 in 14 084. The estimated mortality rate was 1 per 17 857 exposed persons. CONCLUSIONS: The procedural safety and efficacy of the zero-fluoroscopic approach are similar to those of conventional fluoroscopy-based ablation for atrioventricular nodal re-entrant tachycardia and atrial flutter. Under the assumption of low radiation dose, the excessive lifetime risk of malignancy in the CF group due to electrophysiology procedure is reasonably small, whilst totally reduced in zero fluoroscopy procedures.
Keywords: výsledek terapie; Zero fluoro procedures; Effective dose; nodus atrioventricularis; Tachycardia, Atrioventricular Nodal Reentry; Fluoroscopy; Three-dimensional electroanatomical mapping system; atrioventrikulární nodální reentry tachykardie; Supraventricular tachycardias; Prospective Studies; Atrioventricular Node; srdeční arytmie; Radiation exposure; Catheter Ablation; flutter síní; Arrhythmias, Cardiac; Treatment Outcome; lidé; supraventrikulární tachykardie; Humans; Fluoroscopic guidance; Atrial Flutter; Catheter ablation of arrhythmias; katetrizační ablace; Tachycardia, Supraventricular; lidé středního věku; fluoroskopie; Middle Aged; prospektivní studie